WORKING MEMORY DAN KREATIVITAS DALAM PENELITIAN PEMBELAJARAN MATEMATIKA: TINJAUAN LITERATUR SISTEMATIS - Harisuddin, Muhammad Iqbal; Zaenuri, Zaenuri; Sukestiyarno, Yohanes Leonardus; Waluya, St. Budi; Pujiastuti, Emi (Jurnal Muara Pendidikan, 2025)
Research on mathematics learning is increasing and developing. However, empirical research ideas on working memory (WM) and creativity are still very limited. Educators must train students' WM skills in addition to providing reinforcement for mathematics learning. A systematic literature review follows the 10-step approach by Gough et al. The research questions consist of: What are the ideas about the definition, components and abilities of working memory? The idea of ​​Working Memory in mathematics learning related to reasoning, problem solving and creativity? The researcher determined the publication period of the relatively latest articles in 2015 - 2024. The researcher conducted a database search on PsycInfo, MathEduc, Harzing's Publish or Perish and Scopus. Meanwhile, to determine the quality of the journal, the researcher based it on the database on ScimagoJR. After sorting, the articles analyzed were 37 found in 18 different journals. There are six definitions of WM, four related to working memory components, 10 related to working memory abilities, two related to working memory descriptions of reasoning and problem solving, three related to descriptions of creativity and three ideas of WM in mathematics learning, namely arithmetic, geometry and algebra.